Numerical assessment of reinforced concrete beams strengthened with CFRP sheets under impact loading - Mohamed Emara; Nada Elkomy; Hilal Hassan (Fracture and Structural Integrity)
This paper investigates numerically the behavior of Reinforced Concrete (RC) beams, strengthened using Carbon Fiber Reinforced Polymers (CFRP) sheets, subjected to impact loading. Three-dimensional finite element analysis was performed and its results were verified against experimental ones available in the literature showing good agreement. Then, a comprehensive parametric study was performed to investigate the effect of studied parameters on the strengthened RC beams. The main studied parameters were the type and size of reinforcing bars, geometric characteristics of externally bonded CFRP sheets (width, length, and thickness), impact velocity, and the position of the impactor with respect to the beam. Results showed that the use of externally bonded CFRP sheets enhanced the beam capacity and failure mode, and reduced the mid-span deflection. On the other hand, increasing the impact velocity increased the mid-span displacement, however, the use of CFRP bars as internal reinforcement could reduce the increase in the deflection. Moreover, changing the position of the impact load application showed a significant effect on the mid-span displacement as well as the failure mode of tested beams